(3JjSjQ GdhUhd Edi LGeY GdCUhds - (3YHO GdQMef Hf Ydj Hf eMeO Hf YeQ GdOjHL GdTjHGfis; (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO GHf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s ((3YHO GdbGOQ Hf CHj GdaJM Hf YHO GdbGOQ Hf CHj HcQ GdLYaQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi jSQ GdhUhd , Edi LGeY GdCUhd, ef MOjK GdQShd (B" (3U(B" (3, hSgd ai fMh KdK MLeg ENJUGQg eY MSf GdEjQGO s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B:" (3cdeJGf NajaJGf Ydi GddSGf KbjdJGf ai GdejRGf MHjHJGf Edi GdQMef SHMGf Gddg hHMeOg SHMGf Gddg GdYXje , BNQ GdLRA GdKGfi hHJeGeg Je LejY GdcJGH s
(3GdLRA GdKGfi ef GdfSNI GdSGHbI (B" (3hHg JeGe GdcJGH HChdgG agQSJ HChdgG hBNQgG ebGHdGJ hbQGAGJ hSeGYGJ hJedcGJ eJbOeIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfhGfGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdMOjK h GdeUWdMs